Research on the Key Technology Application of Industrial Robot in Grinding and Polishing of Pen and Electronic Industry. (November 2020) - Qi, Yunxia
Abstract: Taking grinding and polishing industrial robot as the research object, three key technologies in the process of machining are analyzed. Firstly, the selection method of grinding mode is introduced. Secondly, the tool calibration and workpiece calibration method in the process of robot running program editing are introduced. Finally, the singularity phenomenon and improvement method in the process of industrial robot operation are introduced. Through the analysis, the optimization of robot in control, programming, process and other technologies can be improved to meet the actual production needs of grinding and polishing robot seek.